Photo‐Assisted Li‐N2 Batteries with Enhanced Nitrogen Fixation and Energy Conversion - Li, Jian‐You; Du, Xing‐Yuan; Wang, Xiao‐Xue; Yuan, Xin‐Yuan; Guan, De‐Hui; Xu, Ji‐Jing (Angewandte Chemie International Edition, 2024)
Li‐N2 batteries have received widespread attention for their potential to integrate N2 fixation, energy storage, and conversion. However, because of the low activity and poor stability of cathode catalysts, the electrochemical performance of Li‐N2 batteries is suboptimal, and their electrochemical reversibility has rarely been proven. In this study, a novel bifunctional photo‐assisted Li‐N2 battery system was established by employing a plasmonic Au nanoparticles (NPs)‐modified defective carbon nitride (Au‐Nv‐C3N4) photocathode. The Au‐Nv‐C3N4 exhibits strong light‐harvesting, N2 adsorption, and N2 activation abilities, and the photogenerated electrons and hot electrons are remarkably beneficial for accelerating the discharge and charge reaction kinetics. These advantages enable the photo‐assisted Li‐N2 battery to achieve a low overpotential of 1.32 V, which is the lowest overpotential reported to date, as well as superior rate capability and prolonged cycle stability (≈500 h). Remarkably, a combination of theoretical and experimental results demonstrates the high reversibility of the photo‐assisted Li‐N2 battery. The proposed novel strategy for developing efficient cathode catalysts and fabricating photo‐assisted battery systems breaks through the overpotential bottleneck of Li‐N2 batteries, providing important insights into the mechanism underlying N2 fixation and storage. A novel bifunctional photo‐assisted Li‐N2 battery system is established by employing a plasmonic Au nanoparticles (NPs)‐modified defective carbon nitride (Au‐Nv‐C3N4) photocathode. Benefiting from the strong light‐harvesting, N2 adsorption, and N2 activation abilities of the Au‐Nv‐C3N4 cathode, the photo‐assisted Li‐N2 battery displays the highest round‐trip efficiency (56.2 %) to date, superior rate capability, and stable cycle life of over 500 h.